2012
DOI: 10.1155/2012/715951
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Urothelial Carcinoma of the Bladder Metastatic to the Stomach: A Case Report

Abstract: Introduction. Plasmacytoid urothelial carcinoma (PUC) of the bladder is a rare histological variant of urothelial carcinoma that was recently identified. Available data on this histological variant is limited. Case Report. We report the case of a 75-year-old man with presumed history of high-grade urothelial cancer of the bladder, treated with transurethral resection and Bacille Calmette-Guérin (BCG) in 2004. Six years after treatment of the bladder cancer, the patient underwent gastrectomy for an undifferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Prominent retraction artifact around each tumor cell may also be seen. [ 3 5 ] Retraction artifacts were seen in the present case too.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Prominent retraction artifact around each tumor cell may also be seen. [ 3 5 ] Retraction artifacts were seen in the present case too.…”
Section: Discussionsupporting
confidence: 60%
“…Plasmacytoid carcinoma of the urinary bladder or plasmacytoid urothelial carcinoma (PUC) is one such rare and only recently described a histological variant of transitional cell carcinoma. It is an aggressive variant and may be confused with plasmacytoma and lymphoma,[ 3 ] a high index of suspicion for both urologist and pathologist is essential to avoid a misdiagnosis. We report here an interesting case of plasmacytoid carcinoma of the urinary bladder in a 52-year-old male, which posed diagnostic difficulties on histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms include: urgency, urinary frequency increase, and low abdominal pain. 8 Metastasis often affects adjacent pelvic structures such as the bones, the peritoneum, the gastrointestinal tract, and the scrotum, 3,6,13,14 and even heart distant metastasis have been described. 15 Ricardo-Gonzalez et al evaluated 15 patients with PUC and found this tumor presenting with recurring extension to the peritoneum, often compromising serous surfaces.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…15 Ricardo-Gonzalez et al evaluated 15 patients with PUC and found this tumor presenting with recurring extension to the peritoneum, often compromising serous surfaces. 16 One of the hypotheses for the aggressiveness of this tumor and its extension pattern is the loss of Ecadherin (a necessary protein for cell to cell adhesion), 6,17 which is absent in most PUCs and can help distinguish it from other types of UCs. 11 It is postulated that the absence of E-cadherin leads to loss of cellular differentiation, allowing the PUC cells to invade the surrounding tissues along the fascial planes and toward the lymph nodes.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation